Exploring Canadian Academic Librarians’ and Archivists’ Research Outside Librarianship and Archival Studies - Hoffmann, Kristin (Partnership, 2025)
Many academic librarians and archivists (L/As) in Canada have research responsibilities as part of their jobs. For some, those responsibilities include research and scholarship in any disciplinary area, including creative works. This study explored the practices and perspectives of academic L/As in Canada with respect to research in areas outside of librarianship or archival studies (LIAS). An invitation to complete an online questionnaire was sent to over 1,800 email addresses and two listservs. The questionnaire asked about the non-LIAS topics that academic L/As have researched, their perceptions about the importance of research outside of LIAS, and barriers or restrictions they may encounter in doing this research. From the 345 usable responses, 85% of respondents have conducted research on LIAS topics, 32% have done non-LIAS research as part of their job, 29% have done non-LIAS research but not as part of their job, and 38% have not done research outside LIAS. Personal interest was the primary reason for doing non-LIAS research. Nearly half of respondents said that doing non-LIAS research and producing or performing creative works were extremely or very important. At the same time, respondents’ comments revealed a range of perspectives about non-LIAS research, including the sense that it is reasonable to have a connection between research and professional work. More attention is needed to develop a shared understanding about the place and value of non-LIAS research.Data from the study are available in Borealis: https://doi.org/10.5683/SP3/SAKC2C.